Deflation, Silent Runs, and Bank Holidays, in the Great Contraction - Hugh Rockoff (Rutgers University, Department of Economics, 2003)
This paper argues that the banking crises in the United States in the early 1930s were similar to the ?twin crises? – banking and balance of payments crises – which have occurred in developing countries in recent years. The downturn that began in 1929 undermined banks that had made risky loans in the twenties. The deflation that followed further weakened the banks, especially in rural areas where deflation in prices and incomes was the greatest. Depositors in those areas began transferring their deposits to banks they regarded as safer, or purchasing bonds. These ?silent runs,? essentially a capital flight, have been neglected in many accounts of the banking crises. But evidence from the Gold Settlement Fund (which recorded interregional gold movements) and from regional deposit movements suggests that silent runs were important, especially in the crucial year 1930. When the crisis worsened, state and local authorities began declaring ?bank holidays,? which limited the right of depositors to make withdrawals, a movement that culminated in the declaration of a national bank holiday by President Roosevelt. In retrospect the policy advocated periodically by the Federal Reserve Bank of New York, the purchase of government bonds on the open market, was right for the country as a whole. But a majority of the Governors of the other Federal Reserve Banks were opposed. Some opponents of open market purchases thought they would benefit the stock market without contributing significantly to the revival of business in the interior. The result was a minimalist policy that led to an unprecedented financial and economic collapse.
Keywords: 330; Bankenkrise; Zahlungsbilanzungleichgewicht; Bankenliquidität; Bankenpolitik; Bankgeschichte; Vereinigte Staaten; bank run